Current progress in biosensors for organophosphorus pesticides based on enzyme functionalized nanostructures: a review. Issue 46 (15th November 2018) - Xiong, Sheng; Deng, Yaocheng; Zhou, Yaoyu; Gong, Daoxin; Xu, Yuzhe; Yang, Lihua; Chen, Henghui; Chen, Ling; Song, Tianwei; Luo, Ao; Deng, Xiaolan; Zhang, Chenyu; et al.
Abstract : Organophosphorus pesticides analysis has become an increasingly significant research area due to their widespread application and contamination of the environment. Abstract : Organophosphorus pesticides analysis has become an increasingly significant research area due to their widespread application and contamination of the environment. With the worsening of environmental contamination, the control of pesticides is important to both human health and environment protection. Distinct from traditional methods of pesticides detection, application of electrochemical biosensors based on enzyme-functionalized nanostructures in the field of pesticides analysis is promising. This review mainly introduces the recent achievements and problems in biosensors based on enzyme-functionalized nanostructures for organophosphorus pesticides detection, such as efficiency and high sensitivity, and meanwhile the problem of practicability is also discussed.